2021
DOI: 10.1097/mao.0000000000003248
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Unilateral Hearing Loss: Characteristics and Etiological Analysis in 121 Patients

Abstract: Objective: To describe the characteristics and etiological analysis in patients with congenital unilateral hearing loss. Study design: Retrospective cohort analysis. Setting: Tertiary referral center. Patients: Children with permanent congenital unilateral hearing loss born between 2007 and 2018. Patients were referred after universal newborn hearing screening or by a colleague to confirm the diagnosis and perform etiological examinations. Main outcome measures: Hearing loss type, severity, and evolution linke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Most cases of UHL are congenital, or early onset [19] and are predominantly sensorineural in nature. Congenital sensorineural UHL is often related to cochlear nerve deficiency (or other structural inner ear anomalies), or congenital cytomegalovirus (CMV) infection, although many other potential origins have been identified [3,16,18]. Congenital conductive UHL in kids accounts for up to one quarter of UHL cases and is primarily related to aural atresia [16,20].…”
Section: Impact Of Unilateral Hearing Loss In Childhoodmentioning
confidence: 99%
See 3 more Smart Citations
“…Most cases of UHL are congenital, or early onset [19] and are predominantly sensorineural in nature. Congenital sensorineural UHL is often related to cochlear nerve deficiency (or other structural inner ear anomalies), or congenital cytomegalovirus (CMV) infection, although many other potential origins have been identified [3,16,18]. Congenital conductive UHL in kids accounts for up to one quarter of UHL cases and is primarily related to aural atresia [16,20].…”
Section: Impact Of Unilateral Hearing Loss In Childhoodmentioning
confidence: 99%
“…Congenital conductive UHL in kids accounts for up to one quarter of UHL cases and is primarily related to aural atresia [16,20]. Progressive, or delayed onset UHL, as might occur with enlarged vestibular aqueduct syndrome or CMV, for example, is also known to occur [16,19,21]. Despite adequate work-up, the cause may remain unknown for a large proportion of children [16,22].…”
Section: Impact Of Unilateral Hearing Loss In Childhoodmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous research on a cohort of children with bilateral/unilateral loss found no significant association between risk indicators and progressive loss except that children with craniofacial anomalies were more likely to have stable hearing loss ( 24 ). Permanent conductive (structural) loss, generally associated with craniofacial anomalies such as aural atresia has been reported in 25%–33% of children with UHL ( 2 , 43 ). Onset of hearing loss, which can be related to etiology, and type and severity of hearing loss at diagnosis have also not been well-investigated in relation to progressive hearing loss.…”
Section: Introductionmentioning
confidence: 99%